Three Lycopodium alkaloids from Thai club mosses. (December 2018) - Nilsu, Thanasan; Thaisaeng, Wachirasak; Thamnarak, Wanlaya; Eurtivong, Chatchakorn; Jumraksa, Apiwan; Thorroad, Sakornrat; Khunnawutmanotham, Nisachon; Ruchirawat, Somsak; Thasana, Nopporn
Abstract: Phytochemical constituents in alkaloid extracts from three Thai club mosses Huperzia squarrosa, Huperzia phlegmaria and Phlegmariurus nummularifolius were investigated. Squarrosinoxide was an undescribed Lycopodium alkaloid from H. squarrosa possessing an unprecedented 6/5/7 tricyclic spiro system. Acetyllycophlegmarianol was an undescribed N -oxide lycopodine-type alkaloid isolated from H. phlegmaria . 4-Epilycopodine, an undescribed epimer of lycopodine, was first isolated from P. nummularifolius . The structural assignments were established through comprehensive spectroscopic techniques and chemical correlations. All compounds were assayed for their anti-acetylcholinesterase activity in vitro . Graphical abstract: Investigation of the methanol extract of Thai club mosses Huperzia squarrosa, Huperzia phlegmaria and Phlegmariurus nummularifolius led to the isolation of three Lycopodium alkaloids with anti-acetylcholinesterase activity. Image 1 Highlights: Squarrosinoxide represented an unprecedented 6/5/7 tricyclic spiro system. Acetyllycophlegmarianol comprised an O -acetyl and N -oxide moieties. 4-Epilycopodine was a 4β-epimer of lycopodine.